Peningkatan Pengetahuan Kader Posyandu tentang Hak dan Kewajiban Ibu Hamil dan pemanfaatan aplikasi “sayang bunda” - Ambar Dwi Erawati; Chusnul Zulaika; Mona Tiorina Manurung (JURNAL PENGABDIAN MASYARAKAT INDONESIA, 2022)
Telemedicine is an alternative health service facility that can help reduce disease transmission. The Semarang City Government issued a “darling mother” application to help pregnant women consult and assist cadres in screening. However, the "dear mother" application has not been used optimally by pregnant women in the city of Semarang. The “Dear Mother” application can prevent accidental violations of the law for pregnant women, so it is necessary to increase knowledge. The method used is to provide classical counseling at the Mangkang Health Center. After the extension of knowledge of cadres increased by an average of 25.35%. The need for counseling to cadres on a regular basis (not just one-time counseling).